Real-time Collision Avoidance and Accident Prevention - A Survey - Prasad, C Krishna; S, Lavanya; Rao, Manikanta S; K, Nandu Rajeshwari; Joseph, A Benjamin (Perspectives in Communication, Embedded-systems and Signal-processing - PiCES, 2018)
With the increasing population in the country, the number of vehicles on road is also increasing. Every household has at least 2 or 3 vehicles, because of which the number of on-road accidents is also in the rise, in spite of government laws being enforced for the safety of the riders. This is due to the fact that rules are not being followed properly and many a times accidents occur with no fault of one of the driver, because most accidents tend to happen when there is collision at the rear end. Hence there is a need of technology in vehicles which detects probable accidents by taking into account various factors around the vehicle and sending appropriate alerts. This paper presents a literature review of various proposed technologies implemented in the previous years and their benefits and drawbacks are listed. A system is proposed which concentrates on the accidents occurring on the rear end, is able to predict them and send suitable alerts to the driver. The system proposed is portable and can be attached to any vehicle. Artificial intelligence in the form of video processing is used which can detect vehicles moving at dangerous speeds, and function in all conditions like day/night time, urban/suburban roads.